Three M'sian universities in top 100 world rankings - Borneo Post, (KK) (Borneo Post (KK), 2016)
KUALA LUMPUR: Three Malaysian universities made it to the top 100 list out of300 universities, involving 50 countries, of the Times Higher Education (THE) BRICS and Emerging Economies University Rankings 2017.